Endothelin antagonist as add-on treatment for proteinuria in diabetic nephropathy: is there light at the end of the tunnel? - Ritz, Eberhard; Wenzel, René R. (Journal of the American Society of Nephrology, 2011)
After the seminal discovery by Yanagisawa et al. [1][1] of the endothelial cell-derived vasopressor endothelin-1 (ET) and eventually the identification of two other isoforms, inhibitors of the ET receptors (ETA, ETB1, and ETB2) were high on the list of therapeutic drugs for the pharmaceutical